Effectiveness of Responsive Teaching With Children With Down Syndrome - KARAASLAN, ÖZCAN (AMER ASSOC INTELLECTUAL DEVELOPMENTAL DISABILITIES, 2013)
A randomized control study was conducted to evaluate Responsive Teaching (RT) with a sample of 15 Turkish preschool-aged children with Down syndrome (DS) and their mothers over a six-month period of time. RT is an early intervention curriculum that attempts to promote children's development by encouraging parents to engage in highly responsive interactions with them. Subjects were randomly assigned to treatment conditions: the control group consisted of standard preschool classroom services; the RT group received bi-weekly RT parent-child sessions in addition to standard services. RT mothers made significantly greater increases in their Responsiveness and Affect as wellas decreases in Directiveness than control group mothers. There were also significant group differences in children's interactive engagement and development. Children in the RT group improved their developmental quotient scores by an average of 47% compared to 7% for children in the control group. Results are described in terms of the effects of parental responsive interaction on the developmental functioning of children with DS.
Keywords: early intervention; relationship-focused intervention; parental responsiveness; developmental learning; Down syndrome; responsive teaching; FOCUSED EARLY INTERVENTION; YOUNG-CHILDREN; MATERNAL RESPONSIVENESS; ADOPTED-CHILDREN; TODDLERS; LANGUAGE; MOTHERS; BEHAVIORS; ABILITIES; VALIDITY